EVALUASI TEKNIK PEMOTONGAN AYAM DITINJAU DARI KEHALALAN DAN KEAMANAN PANGAN DI KABUPATEN TANAH DATAR - DELFITA, RINA (IAIN Batusangkar, 2013)
Evaluation of slaughter chicken technique that observated from halal food and food safety in market in five subdictricts of Kabupaten Tanah Datar was studied. The experiment was used t-test to compare halal slaugtering and bacteria contamination. The results showed that the place expedience was not significantly different between slaughtering place in market. The halal slaugtering practice was not significantly different for those ten places of slaughtering. TPC contamination for all slaughtering place was underneath from standard BMCM of SNI (?1 x 106cfu/g). The Coliform contamination for all slaughtering place was over than 1x102cfu/g, except for Sungai Tarab subdictricts.This evaluation of slaughtering place in markets showed that all slaughtering place did not yet implemented the good slaughtering practice and good sanitation and hygiene practice totally.Key words: slaugtering in market, halal slaughtering, TPC, Coliform